2003
DOI: 10.1046/j.1532-5415.2003.51361.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus Immunity in Long‐Term Care Facilities

Abstract: History of immunization from patients, families, or medical charts may be unreliable indicators of tetanus immunity. Recognizing patterns of and barriers to immunization could have important consequences for public health policy in long-term care institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…These studies demonstrate that vaccination coverage is low and failure to have protective antibody concentrations are frequent. Interestingly, the results were similar for both SENIEUR compatible cohorts and patients in long-term care facilities [72,29]. The protective antibody titer against tetanus and TBE is dependent on both the time point of the last vaccination and age; persons over 60 years of age frequent do not have protective antibody [74].…”
Section: Tetanus Diphtheria Pertussis and Tick-borne Encephalitis mentioning
confidence: 93%
See 1 more Smart Citation
“…These studies demonstrate that vaccination coverage is low and failure to have protective antibody concentrations are frequent. Interestingly, the results were similar for both SENIEUR compatible cohorts and patients in long-term care facilities [72,29]. The protective antibody titer against tetanus and TBE is dependent on both the time point of the last vaccination and age; persons over 60 years of age frequent do not have protective antibody [74].…”
Section: Tetanus Diphtheria Pertussis and Tick-borne Encephalitis mentioning
confidence: 93%
“…Only a few studies have documented the number of persons immunized as well as the efficacy of tetanus, diphtheria and TBE vaccine in elderly persons [71,72,65,73,74,75,29]. These studies demonstrate that vaccination coverage is low and failure to have protective antibody concentrations are frequent.…”
Section: Tetanus Diphtheria Pertussis and Tick-borne Encephalitis mentioning
confidence: 99%
“…There is clear evidence that the decline in innate and adaptive immunity results in dramatically reduced vaccine responses and vaccine longevity in older adults. This phenomenon can be seen in many studies [6][7][8][9][10][11]. Based on the susceptibility to diphtheria in a previous study [19], we used 40 year of age as a cut-off point between young and middle-aged adults.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosenescence or a decline in immune function in aging population is characterized by high susceptibility to infection, high incidence of malignancy and autoimmune diseases, and low antibody response to vaccination [3][4][5]. Low antibody responses has been reported in several studies of vaccinations against influenza [6], pneumococcus [7], hepatitis A [8], herpes zoster [9], yellow fever [10], tickborne encephalitis, tetanus, pertussis and diphtheria [11,12]. The immunosenescence processes in human include decreased ability of neutrophil and macrophage for phagocytosis, decreased oxidative bursts, decreased antigen-presenting cells (APCs) function, and changes in cytokine and chemokine secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence studies in the USA have shown that more than half the adults lack antibody levels that are considered protective against tetanus [64] and support the need to give primary courses and boosters every 10 years, especially to those with tetanus‐prone wounds. Older people have a good response to single administration of a single dose of tetanus vaccine [65].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%